2023
DOI: 10.1038/s41598-023-32353-6
|View full text |Cite
|
Sign up to set email alerts
|

A glucose tolerant β-glucosidase from a newly isolated Neofusicoccum parvum strain F7: production, purification, and characterization

Abstract: Cellulase-producing microorganisms produce low titres of β-glucosidases with low tolerance to glucose. This study aimed to improve production, purify, and characterize a β-glucosidase from a newly isolated Neofusicoccum parvum strain F7. β-Glucosidase production was significantly enhanced by a sequential statistical modelling approach from 1.5-fold in Plackett–Burman design to 2.5 U/ml in the Box–Behnken design compared to the preliminary one variable at a time experiments (1.6 U/ml). The optimal conditions fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…4b showed that Bgl production was favored at lower concentrations of both NaCl and KCl, while Bgl production decreased as both the concentrations were steadily increasing corroborating their negative effects on the Bgl production. Interaction between incubation time and all other tested variables indicated that as incubation time increased, Bgl production These results are corroborated by previous studies where enzyme production was also noted to have steeply declined beyond the optimum incubation time [19][20][21]. Interactions between incubation time and NaCl (CE) were more statistically significant amongst all other tested interactions in this study with the observed p value of 0.0003 (<0.05) (Fig.…”
Section: Optimization By Central Composite Design and Model Validationsupporting
confidence: 91%
See 1 more Smart Citation
“…4b showed that Bgl production was favored at lower concentrations of both NaCl and KCl, while Bgl production decreased as both the concentrations were steadily increasing corroborating their negative effects on the Bgl production. Interaction between incubation time and all other tested variables indicated that as incubation time increased, Bgl production These results are corroborated by previous studies where enzyme production was also noted to have steeply declined beyond the optimum incubation time [19][20][21]. Interactions between incubation time and NaCl (CE) were more statistically significant amongst all other tested interactions in this study with the observed p value of 0.0003 (<0.05) (Fig.…”
Section: Optimization By Central Composite Design and Model Validationsupporting
confidence: 91%
“…However, the conventional optimization approach fails to account for the interplay between the variables utilized and their overall impact on the required output; hence, there is a growing preference for statistical techniques such as response surface methodology (RSM) in the optimization of fermentation processes [20]. This statistical approach decreases the overall number of required experiments and better elucidates the relationships between various elements and the fermentation output [21]. RSM includes Plackett-Burman design (PBD) which efficiently identifies the most influential fermentation components out of many and the central composite design (CCD) which ascertains the ideal concentration of individual components, evaluates their interaction, and also assesses their impact on the response [22].…”
Section: Introductionmentioning
confidence: 99%
“…Concurring with these results, unpurified BGL from a different B. bassiana strain was previously shown to be active under moderately acidic conditions [ 24 ], in addition, most fungal BGLs have been reported to be active at pH 4.0–6.0. Recent examples include the BGL from Aspergillus fumigatus [ 26 ] and Neofusicoccum parvum [ 27 ]. The BGL in this study retained >60 residual activity after 4 h incubation at pH 4.0, 5.0, and 6.0, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal conditions provided by the manufacturer for the commercial cellulase enzyme for optimal activity were 5 U/mg enzyme in (pH 5.0) buffer at 50 °C with 2 h of incubation. Therefore, 0.05 g of microcrystalline cellulose (Sigma, St. Louis, MO, USA) and 5 U/mg of enzyme in sodium phosphate buffer (pH 5.0) were incubated at 50 °C for 2 h. To test the effectiveness of β -glucosidase supplementation in the cellulase cocktail, 0.25 U/mg of purified β -glucosidase from a previous study by Singh et al [ 50 ] was supplemented in the commercial cellulase cocktail and incubated at optimal conditions as described above.…”
Section: Methodsmentioning
confidence: 99%